The Influence of Relational Competence, Work Flexibility, and Technology Mastery on Performance, with Work Commitment as an Intervening Variable - Sinulingga, Desminaria; Meutia; Andriyansah (Dinasti International Journal of Digital Business Management, 2023)
This research aims to: (1) analyze the effect of relational competence on performance; (2) analyze the effect of work flexibility on performance; (3) analyze the effect of mastery of technology on performance; (4) analyze the effect of relational competence on work commitment; (5) analyze the effect of work flexibility on work commitment; (6) analyze the effect of mastery of technology on work commitment; and (7) analyze the effect of work commitment on performance. This research was conducted on the statistical partners of BPS Batu Bara Regency, where the population was 201 people and the number of samples was 67. The sampling technique uses probability sampling techniques. The analysis method uses PLS analysis with the smartPLS 4.0 application. The research results show that relational competence and work commitment directly have a positive and significant influence on performance. Work flexibility and mastery of technology have no effect on performance. Relational competence and mastery of technology have no effect on work commitment. Work flexibility has a positive and significant effect on work commitment. Indirectly, work commitment mediates the influence of work flexibility and mastery of technology on performance, and work commitment is unable to mediate the influence of relational competence on performance.